The properties and formation mechanism of oat β-glucan mixed gels with different molecular weight composition induced by high-pressure processing. - Rui Fan; Peihua Ma; Dan Zhou; Fang Yuan; Xueli Cao (PLoS ONE)
High pressure, an emerging nonthermal technology has been widely applied in food product modifications. The effects of oat β-glucan concentration and pressure on the properties of mixed gels with the different ratios of varying molecular weight (MW) β-gulcan induced by HPP were investigated. The results showed that the lowest β-glucan concentration forming a gel was 15% at 200 MPa, while 8% β-glucan was required to form a gel at 500 MPa. The gel intensity and textural properties increased with elevating β-glucan total concentration and pressure. The characteristic compact and smooth mixed gel formed with 12% β-glucan at a ratio of 50:50 at 400 MPa for 30 min. Under this optimal parameters, the mixed solution showed a relatively lower particle size and turbidity, and the hydrogen bonding and electrostatic interaction played the main role during the gel formation process by high pressure. In addition, the core molecular structure of β-glucan was maintained in the mixed gel formed under the optimal parameters.